The ghosts of computers past. - Wallich, P.
A silicon valley museum-in-the-making showcases a half-century of innovation in computing. The museum at Moffett contains perhaps the most complete collection of groundbreaking hardware and software in the world-from the Hollerith punch-card tabulating machine that rescued the 1890 US census to the LINC laboratory minicomputer to a prototype of the Palm Pilot PDA and an early copy of IBM's gigabyte credit-card-sized disk drive. Preserving all these artifacts is quite an achievement in a field where last year's top-secret supercomputer is next year's scrap.
Keywords: Hollerith punch-card tabulating machine; LINC laboratory minicomputer; Moffett; Palm Pilot PDA; Computing innovation; Credit-card-sized disk drive; Hardware; Silicon valley museum-in-the-making.; Software